2014
DOI: 10.1007/s10661-014-3662-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of heavy metals in surface sediments of northern littoral zone of Lake Çıldır, Ardahan, Turkey

Abstract: In this paper, the heavy metal levels (Cu, Pb, Zn, Ni, Mn, Fe, As, Cd, Cr, Hg), organic carbon, and chlorophyll degradation products were studied to prove their ecological effects in Lake Çıldır, where fossil fuels are used as an energy source in the studied area for most of the year, and domestic waste from settlements is discharged directly into the lake. Sediment samples were collected from six sites on the northern shore of Çıldır Lake, Turkey in November 2012. Enrichment (EF) and contamination factor (CF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 24 publications
1
26
1
Order By: Relevance
“…It is indicated that either groundwater or human pollution elevated the As contents in Yangzonghai Lake sediments. The As contents in Yangzonghai are also higher than that in freshwater lakes of the East China plain, Lake Cildir in Turkey, and Lake Geneva [28][29][30]. The As concentrations in the sediments from Lake Dianchi, however, are generally higher than that of this study, because Dianchi is located near Kunming and was severely polluted [31].…”
Section: Heavy Metal Distributions Of the Samplescontrasting
confidence: 76%
See 1 more Smart Citation
“…It is indicated that either groundwater or human pollution elevated the As contents in Yangzonghai Lake sediments. The As contents in Yangzonghai are also higher than that in freshwater lakes of the East China plain, Lake Cildir in Turkey, and Lake Geneva [28][29][30]. The As concentrations in the sediments from Lake Dianchi, however, are generally higher than that of this study, because Dianchi is located near Kunming and was severely polluted [31].…”
Section: Heavy Metal Distributions Of the Samplescontrasting
confidence: 76%
“…Fig. 5 shows the dendrogram of the samples calculated lacustrine sediment (10)(11)(12)(13)(14)(15)(16)(17) soil (57,61,63,66,67,70,71) lakeside sediment (18,24,33) lakeside sediment (22,(25)(26)(27)(28)(29)32,(37)(38)(39)(40) from the hierarchical cluster analysis. The samples can be classified into five groups.…”
Section: Cluster Analysismentioning
confidence: 99%
“…Source and migration of metals may be reflected by correlation analysis and PCA [49,50]. Non-significant correlation between Fe-Mn, Fe-Cr, Mn-Cu, Cu-Zn, Mn-Pb, Cu-Cr, Cu-Ni, Cr-Pb, and Pb-Co indicates different factors controlling the availability and concentrations of these metals [4,9]. This implies the metals might have originated from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…However, biological and chemical factors influence the mobility of heavy metals in aquatic environments by desorption from sediments into the surface water [7]. This made the surface water a major intermediate source of metal pollutants in benthic sediments, which is the definitive receptor [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This value is obtained from the ratio between the measured concentration of metal/ Al and that in background values within the lake sediments. In this study, the background values of lake sediments from Kükrer et al (2014) were used and the following scale of Sutherland (2000) was considered in assessing the enrichment factor: EF<2, deficiency to minimal enrichment EF=2-5, moderate enrichment EF=5-20, significant enrichment EF=20-40, very high enrichment EF>40, extremely high enrichment Another method used to ascertain contamination levels was the contamination factor (CF), which is the ratio of metal concentration to the background metal concentration. This was classified into four divisions (Hakanson 1980), as follows: To determine the environmental quality of the sediments, pollution load index (PLI) was used (Suresh et al 2011), which is calculated considering all metals present to ascertain the level of toxicity in the material being examined.…”
Section: Sampling and Analysesmentioning
confidence: 99%